Multikulturalisme dalam Sejarah Islam - Riswan; Albina, Meyniar (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The aim of this research is to find out how multiculturalism is in the history of the Islamic Ummah. This type of research uses a qualitative approach. The approach used is a descriptive study. According to Suharsimi in Aiman Faiz, a descriptive approach is research carried out to obtain information related to existing status or symptoms. Multiculturalism is a term used to explain a person’s view of the diversity of life in the world, or a cultural policy that emphasizes acceptance of the reality of diversity and the various kinds of cultures (multiculturalism) that exist in people’s lives regarding values, systems, culture, habits and In the politics they adhere to, Islam is a universal religion that upholds human values, equal rights and recognizes the existence of diverse cultural backgrounds and pluralism. Multiculturalism according to Islam is a rule of God (sunnatullah) that will not change, nor can it be opposed or denied.